2019
DOI: 10.1109/mce.2019.2892245
|View full text |Cite
|
Sign up to set email alerts
|

Technology in the Hospitality Industry: Prospects and Challenges

Abstract: The leisure and hospitality industry is one of the driving forces of the global economy. The widespread adoption of new technologies in this industry over recent years has fundamentally reshaped the way in which services are provided and received. In this paper, we explore some of the state-of-theart technologies currently employed in the hospitality industry and how they are improving guest experiences and changing the hospitality service platform. We also envision some potential future hospitality services w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
36
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 78 publications
(38 citation statements)
references
References 11 publications
(15 reference statements)
1
36
0
1
Order By: Relevance
“…The study findings confirmed the positive influence of technology convenience on PEOU [ 29 , 66 , 69 ]. Perceived enjoyment also showed a significant positive influence on PEOU [ 27 , 28 , 71 ].…”
Section: Discussion Implications and Limitations Of The Studysupporting
confidence: 71%
See 1 more Smart Citation
“…The study findings confirmed the positive influence of technology convenience on PEOU [ 29 , 66 , 69 ]. Perceived enjoyment also showed a significant positive influence on PEOU [ 27 , 28 , 71 ].…”
Section: Discussion Implications and Limitations Of The Studysupporting
confidence: 71%
“…Some researchers highlighted that social media is being increasingly used as a source for information search and for spreading awareness, but it is unclear which factors increase the use of social media for travel planning [ 1 , [21] , [22] , [23] ]. Further, there are limited studies on tour and travels that have hypothesized the relationship considering various key variables such as perceived enjoyment, technology convenience and media richness in the framework developed and also tested outside of India [ [27] , [28] , [29] ]. Yet, a theoretical framework underpinning and predicting the use of SM in general for travel planning remains still missing.…”
Section: Introductionmentioning
confidence: 99%
“…Successful companies invest substantial amount of time, money and efforts in its cultures because they have experienced its benefits. They know that corporate culture is a strategic asset, it improves the level of guest service, the number of their hotel visits, thus increasing the company's net profit [10]. The main functions of corporate culture of the company are image formation, maintaining the values, support of new employees in socialization, the establishment of rules and values of behavior, formation of the sense of belonging to common cause on the part of the employees.…”
Section: Methodsmentioning
confidence: 99%
“…The study also identified the main drivers of digitalization in the tourism industry with the help of the structural equation modeling technique. Kansakar et al [113] suggested that the adoption of ICT by the hospitality industry has reshaped the way the industry is providing services. The study concluded that there is a need for updating of technological background of institutions providing the services to enable them to meet the changing environment of the industry.…”
Section: Trends In Technology and Tourism Researchmentioning
confidence: 99%